New species of Lepidocyrtus (Collembola, Entomobryidae) from Italy with a discussion of characters defining European Lepidocyrtus lignorum-group - Mateos, Eduardo; Zhang, Bing; Álvarez-Presas, Marta (Zootaxa, 2023)
Springtails are a group of hexapods whose true diversity is currently underestimated. This is because the morphological characters normally used in species diagnosis do not have the necessary resolution. This situation is especially evident in Entomobryidae, which is currently the most diverse family of springtails. The combination of morphological and molecular data has allowed us to describe a new species of the genus Lepidocyrtus, based on specimens from Northern Italy, as well as to redefine the diagnosis of the European Lepidocyrtus lignorum-group.